A randomized, double‐blind, placebo‐controlled phase II study of eculizumab in patients with refractory generalized myasthenia gravis. Issue 1 (30th April 2013) - Howard, James F.; Barohn, Richard J.; Cutter, Gary R.; Freimer, Miriam; Juel, Vern C.; Mozaffar, Tahseen; Mellion, Michelle L.; Benatar, Michael G.; Farrugia, Maria Elena; Wang, Jing Jing; Malhotra, Suneil S.; Kissel, John T.; et al.
ABSTRACT Introduction: Complement activation at the neuromuscular junction is a primary cause of acetylcholine receptor loss and failure of neuromuscular transmission in myasthenia gravis (MG). Eculizumab, a humanized monoclonal antibody, blocks the formation of terminal complement complex by specifically preventing the enzymatic cleavage of complement 5 (C5). Methods: This study was a randomized, double‐blind, placebo‐controlled, crossover trial involving 14 patients with severe, refractory generalized MG (gMG). Results: Six of 7 patients treated with eculizumab for 16 weeks (86%) achieved the primary endpoint of a 3‐point reduction in the quantitative myasthenia gravis (QMG) score. Examining both treatment periods, the overall change in mean QMG total score was significantly different between eculizumab and placebo (P = 0.0144). After assessing data obtained from all visits, the overall change in mean QMG total score from baseline was found to be significantly different between eculizumab and placebo (P < 0.0001). Eculizumab was well tolerated. Conclusion: The data suggest that eculizumab may have a role in treating severe, refractory MG. Muscle Nerve, 2013